Penggunaan Model Pembelajaran Tapang dalam Meningkatkan Keterampilan Berpikir Kreatif dan Kerja Sama Siswa - Ni Wayan Setiyawati Astin Bakti; Akhmad Riandy Agusta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The low creative thinking skills and cooperation skills of elementary school students are still a challenge in 21st century mathematics learning. Based on the results of observations in grade V of SDN Pasar Lama 3 Banjarmasin, only 32% of students have creative thinking skills and 46% of students have good cooperation skills. This study aims to describe and analyze the application of the TAPANG learning model integrated with Problem Based Learning (PBL), Think Pair Share (TPS), and Talking Stick in improving students' creative thinking and cooperation skills on fractions. This study uses a qualitative approach with the type of Classroom Action Research (CAR) which is implemented in four meetings through the stages of planning, action implementation, observation, and reflection. The subjects of the study were 28 grade V students of SDN Pasar Lama 3 Banjarmasin in the second semester of the 2025/2026 academic year. Data were collected through observations and tests, then analyzed descriptively qualitatively and quantitatively. The results showed that students' creative thinking skills increased from 18% to 86%, while cooperation skills increased from 18% to 86%. These findings indicate that the TAPANG model is effective in creating active, interactive, and collaborative learning and is able to improve the creative thinking and cooperation skills of elementary school students.